2015
DOI: 10.1016/j.apsusc.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of co-evaporated blend films based on initial growth for organic photovoltaics

Abstract: Bulk heterojunction structures composed of electron donor and acceptor molecules for application in high-performance organic photovoltaics studied. To fabricate these structures, the co-evaporation method in vacuum is commonly applied; however, the details of the crystal growth process during co-evaporation have not yet been established. Here, we focused on structural analysis of blend films composed of phthalocyanine and fullerene based on initial growth stage. Similar crystal growth behavior to that typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In another instance, Shibata et al demonstrated a multilayered composite of ZnPc/C 60 which showed a rise in the power conversion efficiency of organic solar cell from 1.2% to 3.0%. [71] Using thermal coevaporation followed by thermal annealing technique, Singhal et al [72] also synthesized Au-C 60 nanocomposite and demonstrated that the gold deposition rate could be tuned to obtain 2 at% with 1.5 nm thickness. C/Pd films were developed by Rymarczyk et al [73] with pristine C 60 and palladium acetate as the precursors by the simultaneous thermal decomposition at low pressure.…”
Section: Evaporation Methodsmentioning
confidence: 99%
“…In another instance, Shibata et al demonstrated a multilayered composite of ZnPc/C 60 which showed a rise in the power conversion efficiency of organic solar cell from 1.2% to 3.0%. [71] Using thermal coevaporation followed by thermal annealing technique, Singhal et al [72] also synthesized Au-C 60 nanocomposite and demonstrated that the gold deposition rate could be tuned to obtain 2 at% with 1.5 nm thickness. C/Pd films were developed by Rymarczyk et al [73] with pristine C 60 and palladium acetate as the precursors by the simultaneous thermal decomposition at low pressure.…”
Section: Evaporation Methodsmentioning
confidence: 99%